2018
DOI: 10.1111/apt.14919
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world clinical, endoscopic and radiographic efficacy of vedolizumab for the treatment of inflammatory bowel disease

Abstract: Vedolizumab was effective for induction and maintenance of clinical and objective remission, both in Crohn's disease and ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
45
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 33 publications
(43 reference statements)
9
45
3
Order By: Relevance
“…Other authors found no difference in CD and UC cohorts after the induction phase, while in one study a higher clinical benefit in patients with UC was seen, with a cumulative clinical remission plus response rate after 14 weeks of 91.2% in UC and 78.5% in CD ( P = 0.02). Again, at 52 weeks the trend of the response in our study was favorable to CD patients despite a lack of statistical significance; in other real‐life studies, the two groups were comparable or there were higher response rates in UC . In addition, despite the better clinical results in CD, our endoscopic remissions at 52 weeks (15% UC and 27% CD) were very low compared with the other available data (41% of UC and 63% of CD in the VICTORY studies and 25.9% of CD and 47.8% of UC patients in a large Canadian cohort).…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…Other authors found no difference in CD and UC cohorts after the induction phase, while in one study a higher clinical benefit in patients with UC was seen, with a cumulative clinical remission plus response rate after 14 weeks of 91.2% in UC and 78.5% in CD ( P = 0.02). Again, at 52 weeks the trend of the response in our study was favorable to CD patients despite a lack of statistical significance; in other real‐life studies, the two groups were comparable or there were higher response rates in UC . In addition, despite the better clinical results in CD, our endoscopic remissions at 52 weeks (15% UC and 27% CD) were very low compared with the other available data (41% of UC and 63% of CD in the VICTORY studies and 25.9% of CD and 47.8% of UC patients in a large Canadian cohort).…”
Section: Discussioncontrasting
confidence: 82%
“…Again, at 52 weeks the trend of the response in our study was favorable to CD patients despite a lack of statistical significance; in other real‐life studies, the two groups were comparable or there were higher response rates in UC . In addition, despite the better clinical results in CD, our endoscopic remissions at 52 weeks (15% UC and 27% CD) were very low compared with the other available data (41% of UC and 63% of CD in the VICTORY studies and 25.9% of CD and 47.8% of UC patients in a large Canadian cohort). A possible explanation for these findings may be the high percentage of patients with severe disease and patients with anti‐TNF experience at baseline in our cohort.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations